Diagnosis of cancer in general practice : a study of delay problems and warning signals of cancer, with implications for public cancer information and for cancerdiagnostic strategies in general practice - Holtedahl, Knut A. (Universitetet i Tromsø, 1991)
Early diagnosis of cancer is beneficial to most cancer patients. This doctoral thesis is based on studies in general practice in Tromsø, Norway, during the years 1978-1985. General practitioners have a very important role in the work excluding or leading up to a cancer diagnosis. The studies deal with diagnostic delay, the value of symptoms, and with strategies for GP s to improve their cancer diagnostic work.